TEACHING READING USING TALKING STICK - Khodijah, Siti; Labibah, Labibah (PROJECT (Professional Journal of English Education), 2019)
Language is the most important aspect in human interaction. People communicate and interact with other using the language. In global community, English has become an international language that is used by many people around the world. Reading is one of English language skills and it is one of the ways to learn English. Reading activity should get more attention. It is because there are many students who get some difficulties in understanding a text. In this research inform the using of talking stick in teaching reading. The objective of this research was to find out whether there was any significant difference in improvement the reading ability of recount text of the tenth grade students of SMK Rosma Karawang in academic year 2018/2019 by using talking stick method. The method used was quantitative method. In this research the writer used pre-experimental design of one group pretest and posttest. The data were analyzed by using paired sample test and processed by using SPSS 23 for windows. The results of the research showed there was significant increase of student’s reading ability.Keywords: Teaching, Reading, Talking Stick